Spatial and temporal patterns of soil salinization in shallow groundwater environments of the Bahía Blanca Estuary: Influence of topography and land use - Celleri, Carla (2021)
Soil salinization is considered an environmental threat as high salt content hinders plant growth.Soil salinity is usually associated with climate aridity at a regional scale, while topography,subsurface hydrology and land use combine with climate to produce salinization patterns atlandscape scale. In this study, the first assessment for the study area on the relationship betweenclimate, groundwater level (GWL) changes and soil salinity was provided. For comparison, twoadjacent vegetation units used as marginal grazing lands were selected: thickets of Allenrolfeapatagonica (Ap thicket), located at the base of a scarp, and bushes of Cyclolepis genistoides (Cgbush), located away from the topographic discontinuity. Electrical conductivity (ECrs) mapsderived from Landsat 8/OLI were used to analyze salinity patterns. The results showed thatGWL rose in coincidence with precipitation events and fell during dryer and warmer periods.GWL was always closer to the surface in the Ap thicket, and level changes were more likely tooccur there. ECrs showed a seasonal pattern with significantly higher (p<0.05) values in the Apthicket during summer. Within the Cg bush, relatively higher ECrs appeared around a permanentwater trough. Within this zone, ECrs values during summer were significantly higher (p<0.05).Coupled evaluation of GWL dynamics and soil salinization patterns showed that GWL changesinteract with land use practices to produce local-scale patterns of salinization. Topographyplayed an important role in controlling soil surface properties through its influence on groundwater dynamics and small topographic changes produced largely different conditions forvegetation growth.